2007
DOI: 10.1111/j.1540-8159.2007.00901.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Short QT Interval

Abstract: Of the 19,153 subjects in this study, none were identified as having the short QT syndrome, with associated high risk of ventricular tachyarrhythmia, atrial fibrillation, and sudden death. Two subjects were identified as having QTc of less than 350 ms, and allowed prevalence and incidence estimates to be made of short QT interval. There observations were suggestive of clinical relationships between short QT interval and organic or electrophysiological heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 15 publications
1
15
0
1
Order By: Relevance
“…The population prevalence of LQTS (1:2,000 to 1:5,000) [Goldenberg et al, 2008;Crotti et al, 2008] is higher than that of SQTS, which was determined to be very low in population screening studies using shortened rate-corrected-QT (QT c ) interval as a screening parameter [Rautaharju et al, 1992;Funada et al, 2008;Moriya et al, 2007;Anttonen et al, 2007]. LQTS is also associated with highly variable expressivity [Vincent et al, 1992] and incomplete penetrance ; but the small number of SQTS families precludes a detailed assessment of penetrance patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The population prevalence of LQTS (1:2,000 to 1:5,000) [Goldenberg et al, 2008;Crotti et al, 2008] is higher than that of SQTS, which was determined to be very low in population screening studies using shortened rate-corrected-QT (QT c ) interval as a screening parameter [Rautaharju et al, 1992;Funada et al, 2008;Moriya et al, 2007;Anttonen et al, 2007]. LQTS is also associated with highly variable expressivity [Vincent et al, 1992] and incomplete penetrance ; but the small number of SQTS families precludes a detailed assessment of penetrance patterns.…”
Section: Introductionmentioning
confidence: 99%
“…In the large Finnish population study, a QT c value Ͻ340 ms was observed in 0.4% of the population, whereas a QT c value Ͻ320 ms was found in just 0.1% (6). This low frequency of extremely short QT intervals was further corroborated by multiple additional studies that demonstrated similar findings (7)(8)(9)11,39). Accordingly, patients with a QT c value less than 350 ms receive 2 points, whereas 3 points are assigned for a QT c value Ͻ330 ms. Of note, patients should not receive points in the presence of modifiable factors known to abbreviate the QT interval such as hypercalcemia, digoxin administration, and androgen use (40 -42).…”
Section: Figure 1 Cellular Mechanism Of Short Qt Intervalmentioning
confidence: 82%
“…This concept is highlighted in a long-term follow-up study of healthy Finnish individuals with short (Ͻ340 ms) and very short (Ͻ320 ms) QT c values who had no documented arrhythmic events after an average follow-up of 29 years (6). Additional studies examining subjects with short QT intervals from the general population have revealed similarly benign outcomes with no evidence of increased arrhythmic risk (7)(8)(9). These findings suggest that the presence of a short QT interval in isolation is not always predictive of an increased arrhythmic risk and therefore should not invariably lead to a diagnosis of SQTS.…”
mentioning
confidence: 99%
“…Even if the prevalence of Short QT Syndrome accompanying lethal arrhythmias is rare, [9][10][11][12] it is important that cardiologists keep this syndrome in mind when caring for the non-structural heart disease patients with syncope or aborted cardiac arrest. Therefore the clinician must keep up with the most recent information on Short QT Syndrome.…”
Section: Discussionmentioning
confidence: 99%